A new technique for improving performance of active power filter in power systems with isolated neutral point - Fereidouni, A.; Masoum, Mohammad Sherkat (2015)
A Hysteresis current control (HCC) modulation is commonly used because of its various advantages. However, the HCC modulation has the disadvantage that the modulation frequency varies in a fixed band and, consequently, produces non-optimum current ripples. To overcome this drawback, an adaptive hysteresis-band current control (AHCC) modulation has been suggested. However, when the AHCC is employed in isolated neutral point (INP) systems, interphases dependency causes very high-switching frequencies. This paper aims to improve the performance of active power filters (APF) that use the AHCC modulation in INP systems. Initially, the AHCC is designed associated with the APF and power system parameters. Then, a new simple approach is proposed in the APF control system to improve the performance of the AHCC modulation technique which will accordingly enhance the APF operation. Detailed simulations are performed to demonstrate the effectiveness of the proposed method.